PREPARATION, CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF XANTHONE-LOADED MAKING (HODGSONIA HETEROCLITA) MICROEMULSIONS - Chansakaow, Sunee; Sirisa-ard, Panee; Khonkarn, Ruttiros (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of this study was to incorporate xanthone into Making (Hodgsonia heteroclita) microemulsions and to evaluate the antioxidant activity of the formulations. Methods: Making oil was obtained from the seed of Hodgsonia heteroclite by a screw press machine. The solubility of xanthone in various oils, surfactants, and co-surfactants was investigated. Stable Making microemulsion and microemulsion-based gel were simultaneously loaded with xanthone. Finally, an in vitro xanthone release study was carried out and antioxidant activity was determined. Results: The optimal formulations of the Making microemulsion consisted of Making oil, capryol 90, tween 80, propylene glycol, and water. The average droplet size of xanthone-loaded Making microemulsion was around 110–130 nm. It was found that the stability of the xanthone-loaded Making microemulsion-based gel was higher than the xanthone-loaded Making microemulsion. Besides, the release of xanthone from the Making microemulsion-based gel was lower than that of the Making microemulsion. Moreover, it was found that the antioxidant activity of both xanthone-loaded Making microemulsion (TEAC and EC values of 9.8 mmol/mg and 14.8 mmol/mg, respectively) and microemulsion-based gel (TEAC and EC values of 9.4 mmol/mg and 18.5 mmol/mg, respectively) remained high even after extended storage conditions. Conclusion: It was concluded that Making oil is an attractive material to deliver xanthone in pharmaceutical applications.